Quantification of tapentadol in rat plasma by HPLC with photo diode array detection: Development and validation of a new methodology - B. Mohammed Ishaq; D. China Babu; Sreenivasulu Munna; Hindustan Abdul Ahad (SpringerOpen, 2017)
Objective: The aim of the present study was to develop and validate a simple HPLC-PDA based method to quantify TAP in rat plasma. Several parameters both in the extraction and detection method were evaluated. The applicability of the method was determined by administering TAP orally to six albino Wister rats. Methods: The protocol yielded the expected pharmacokinetic results and plasma collected by retro orbital vein puncture at regular intervals. The mobile phase consisted of 0.1 M Dipotassium Phosphate buffer (pH 6.8) and acetonitrile in the ratio of 50:50 v/v with a flow rate of 1.2 mL min−1. The detection wavelength was 241.0 nm. TAP was extracted from the plasma using a mixture of Ethanol: Dichloro methane (70:30 v/v), which gave a recovery of 99.0-101.8%. Results: The linearity of the method for both tapentadol and tramadol demonstrated correlation coefficients (R2) above 0.99 and linear range from 9.775 to 5024.376 ng/mL for tapentadol and 100 to 500,000 ng/mL for tramadol. The lower limits of quantitation (LLOQ) were found to be 9.775 ng/mL for tapentadol, and the upper limit of quantitation (ULOQ) was determined to be 5024.376 ng/mL. The chromatographic runs were specific with no interfering peaks at the retention times of the analyte (tapentadol) and ARE (tramadol), as confirmed by HPLC-PDA experiments. Conclusion: In conclusion, this was a simple and effective method using HPLC-PDA to detect TAP in plasma, which may be useful for future pharmacokinetic studies.